Resonant tunneling of electrons in quantum wires (Review Article): Квантовые жидкости и квантовые кpисталлы - Krive, I.V.; Palevski, A.; Shekhter, R.I.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
We considered resonant electron tunneling in various nanostructures including single wall carbon nanotubes,molecular transistors and quantum wires formed in two-dimensional electron gas. The review starts with a textbookdescription of resonant tunneling of noninteracting electrons through a double-barrier structure. The effects of electron–electron interaction in sequential and resonant electron tunneling are studied by using Luttinger liquid model of electron transport in quantum wires. The experimental aspects of the problem (fabrication of quantum wires and transport measurements) are also considered. The influence of vibrational and electromechanical effects on resonant electron tunneling in molecular transistors is discussed.